Global trends of Vaccinia oncolytic virus therapy over the past two decades: Bibliometric and visual analysis - Bo, Liu; Tianming, Liu; Fengliang, Fan; Wenping, Liang; Jinzuo, Han; Dongbo, Xue; Biao, Ma; Haijun, Sun (Frontiers in Immunology, 2023)
Background In recent years, the vaccinia oncolytic virus has entered the clinical trial stage of examination and shown good progress. It has many advantages, such as good safety, high oncolytic efficiency, and the regulation ability of the tumor microenvironment, and is expected to be successfully used in the clinical treatment of tumors in the future. However, no bibliometric analysis has so far been performed that generalizes horizontally across this field. Therefore, this study aims to assess the research status and trends in this field from a global perspective to help guide future research priorities. Methods In this study, the literature related to vaccinia oncolytic virus published in English on Web of Science from 2002 to 2022 was retrieved, and the bibliometric indicators were analyzed using the Histcite. Pro 2.0 tool, while VOSviewer was used to visualize the research trends and hotspots in this field. Results In total, 408 related studies were included. In the past 20 years, the number of related publications in this field has increased year by year, and breakthroughs were made in this field in 2008 and 2013. The research has grown rapidly since 2008, and will likely continue to expand in the years to come. The United States plays a leading role in this area. “MOLECULAR THERAPY-ONCOLYTICS”, “MOLECULAR THERAPY” and “JOURNAL OF TRANSLATIONAL MEDICINE” are core journals that publish high-quality literature on the latest advances in the field. Some authors with numerous high-quality publications include Bell JC and Szalay AA. At present, the research hotspot in this field focus on the clinical application of vaccinia oncolytic virus. Conclusion Overall, the number of vaccinia oncolytic virus-related studies is growing rapidly, in relation to which the United States is the most influential country. The clinical application of vaccinia oncolytic virus will affect the crucial development of future research.